Pengelolaan Mata Pelajaran Pendidikan Agama Islam untuk Meningkatkan Keteladanan Spiritual Guru pada Sekolah Dasar Rahmat Islamiyah Medan - Ahmad Afandi; Danny Abrianto; Tumiran Tumiran (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study aims to analyze the management of Islamic Religious Education (PAI) subjects in enhancing teachers’ spiritual role-modeling at Rahmat Islamiyah Elementary School, Medan. The research employed a qualitative approach using field study methods, including observation, interviews, and documentation. The findings indicate that the systematic management of Islamic Religious Education (PAI), encompassing planning, implementation, and evaluation, plays a pivotal role in shaping teachers’ attitudes and behaviors as spiritual role models for students. Teachers function not merely as transmitters of knowledge but as exemplars of moral and spiritual integrity in their daily school interactions. Furthermore, the study reveals that teachers who consistently apply holistic management practices demonstrate strong spiritual discipline both within and beyond the classroom. Strengthening the management of Islamic Religious Education therefore enhances teachers’ capacity for spiritual exemplarity and contributes significantly to the development of students’ religious character.